Leaf dry mass per unit area and leaf pigments underlying the higher stomatal conductance of deciduous species relative to evergreen species in Dendrobium - Feng-Ping Zhang; Xiao-Di Zhao; Li-Jun Han; Han-Run Li (Botanical Studies)
Abstract Background Leaf stomatal conductance is an important indicator of photosynthetic capacity. However, stomatal conductance is poorly quantified and rarely explored in the context of the leaf functional traits for epiphytes, particularly when it comes to herbaceous species with different leaf habits (deciduous vs. deciduous species). Here, we investigated leaf stomatal conductance, leaf dry mass per unit area, leaf thickness, stomatal density, abaxial epidermal cell size and pigment contents in 23 Dendrobium evergreen and deciduous species from a greenhouse. Our main objectives were to compare differences in all measured traits between evergreen and deciduous species, and to determine the relationships of leaf stomatal conductance with leaf functional traits and leaf pigments. Results The results showed that the evergreen species of Dendrobium had thicker leaves and higher leaf dry mass per unit area, whereas deciduous species had higher leaf stomatal conductance and higher leaf chlorophyll contents. Leaf stomatal conductance had a negative correlation with leaf thickness, and dry mass per unit area, but a positive correlation with leaf pigment contents. There was a negative correlation between pigment contents and leaf dry mass per unit area. Conclusion The results reveal the clear differences in leaf stomatal conductance, leaf functional traits and leaf pigments between deciduous and evergreen Dendrobium species, with the form groups showing trait values indicative of less investments in structural components and of more investments in photosynthetic carbon gain. Furthermore, leaf dry mass per unit area and leaf pigments play an important role in shaping leaf stomatal conductance.